Chromatographic profile and allelopathic potential of the essential oil of Acritopappus confertus (Gardner) R. M. King & H. Rob. (Asteraceae) (Research, Society and Development, 2020)
The present study aims to test the Acritopappus confertus (Gardner) R. M. King & H. Rob. essential oil allelopathic potential on the germination and inital development of Cenchrus echinatus L. and Lactuca sativa L. seedlings, in addition to identifying and quantifying chemical constituents. The chemical composition analysis was performed by gas chromatography (GC-FID) and gas chromatography coupled to mass-spectrometry (GC-MS). For the allelopathic assays, the essential oil was emulsified with dimethylsulfoxide (DMSO) in a 1:1 ratio, and diluted in distilled water to obtain 0.001, 0.01, 0.10, 0.25, 0.50, 0.75 and 1% c. The control consisted of 1% aqueous DMSO solution.Treatments were performed in five repetition with 20 seeds each. The pH of the oils were measured and adjusted to a scale of 6 to 7. Assays were conducted in a germination chamber at 25 °C with a 12h photoperiod. Seed germination, Germination Speed Index (GSI), caulicle and radicle length were analyzed. The data were subjected to analysis of variance and the means were compared by Tukey test (p